Application of Customary Law in the Indonesian Criminal Law Framework after the Enactment of Law Number 1 of 2023 concerning the Criminal Code - Riyanto, Riyanto; Waluyo, Bambang; Harefa, Beniharmoni (Journal of Progressive Law and Legal Studies, 2025)
Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code (New Criminal Code) was finally passed as a substitute for the old Criminal Code or Law Number 1 of 1946 concerning Criminal Law Regulations; in the new Criminal Code, several articles have received pros and cons in the community, one of which is related to the inclusion of articles on laws that live in society (Customary Law). The purpose of this study is to examine and analyze carefully the role of customary Law in the specifics of criminal Law after its inclusion in the new Criminal Code so that we can find out about its position as a law that was once known as unwritten Law into written Law. The legal research method used is normative juridical legal research, which is conducted on library materials using the statute, conceptual, case, and historical approaches. The results of the research that the author has obtained that the Law that lives in the community (Customary Law) in the specific criminal Law in the new Criminal Code will be made a Government Regulation (PP) as the implementation of the regulation so that it can be used as a guideline for the Regional Government in making Regional Regulations (PERDA) on the Law that lives in the community (Customary Law) and researchers also provide the concept of applying the Law that lives in the community (Customary Law) with the approach of the principle of restorative justice for law enforcement officials in carrying out their duties as representatives of the state related to the process of enforcing customary criminal Law.